2009
DOI: 10.1155/2009/974182
|View full text |Cite
|
Sign up to set email alerts
|

Laser Beam Welding of AA5052, AA5083, and AA6061 Aluminum Alloys

Abstract: The present investigation was mainly concerned with characteristics of autogeneous laser butt welding of 2 mm thickness nonheat treatableAA5052-H12,AA5083-H12 and 2 mm, 3 mm thickness heat treatableAA6061-T6aluminum alloys. The effect of laser welding parameters, surface cleaning, filler wire addition, and backing strip on quality of laser welded joints was clarified using 5 kW laser machine. It was found that all the investigated alloys showed tendencies for porosity and solidification cracking, particularly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(34 citation statements)
references
References 14 publications
0
33
0
1
Order By: Relevance
“…Therefore, further research is required on other Al alloys in order to understand the effect of laser cleaning on weld defects such as porosity since it is one of the most common problems faced in aluminium welding using high energy beams such as laser and electron beams. In the previous work, some researchers discussed the effect of mechanical and chemical cleaning of the surface on laser welding using a filler wire [25][26][27] , while others discussed laser cleaning effect on autogenous Al welding 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, further research is required on other Al alloys in order to understand the effect of laser cleaning on weld defects such as porosity since it is one of the most common problems faced in aluminium welding using high energy beams such as laser and electron beams. In the previous work, some researchers discussed the effect of mechanical and chemical cleaning of the surface on laser welding using a filler wire [25][26][27] , while others discussed laser cleaning effect on autogenous Al welding 4 .…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the weld beads were narrower and deeper with an increase in the power density. El-Batahgy and Kutsuna [12] clarified the effect of welding parameters on the porosity level and solidification cracking and they found that the tendencies for porosity and solidification cracking were increased at high welding speed conditions. Chang et al [13] showed that the welding defect rate of the pulsed wave type was larger than that of the continuous type, and the crack rate was reduced with decreasing welding speed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to determine the influence of the welding parameters including laser power, welding speed and defocusing distance (4,5) on weld morphology as well as to identify the sources of welding defects. It would then be possible to identify the optimum combination of welding parameters which ensures the required weld quality and properties, and also minimises welding defects (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%